2000
DOI: 10.1111/j.1471-0528.2000.tb13271.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between placental bed biopsy findings, vascular cell adhesion molecule and fibronectin levels in pre‐eclampsia

Abstract: Objective To determine the correlation between placental bed biopsy findings, and blood levels of the vascular cell adhesion molecule (VCAM-1) and fibronectin in pre-eclampsia/eclampsia, and to evaluate the relationship between these variables and severity of the disease.Design A prospective case-control study.Setting Department of Obstetrics and Gynaecology, Cerrahpasa Medical Faculty, Istanbul.Sample Thirty-five women with pre-eclampsideclampsia were compared with 25 healthy women with uncomplicated pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 17 publications
(27 reference statements)
1
34
0
4
Order By: Relevance
“…Notably, most of the inconsistencies have occurred among those studies that sought to assess maternal sVCAM-1 concentrations in pre-diagnostic blood samples [19,[21][22][23]. Results from case-control studies [17][18]20], where sVCAM-1 concentrations were determined in blood samples collected after the diagnosis of preeclampsia, have been more consistent. In their study, Higgins et al [22] noted no difference in maternal plasma sVCAM-1 concentrations (plasma samples were collected between 18 and 24 weeks' gestation).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Notably, most of the inconsistencies have occurred among those studies that sought to assess maternal sVCAM-1 concentrations in pre-diagnostic blood samples [19,[21][22][23]. Results from case-control studies [17][18]20], where sVCAM-1 concentrations were determined in blood samples collected after the diagnosis of preeclampsia, have been more consistent. In their study, Higgins et al [22] noted no difference in maternal plasma sVCAM-1 concentrations (plasma samples were collected between 18 and 24 weeks' gestation).…”
Section: Discussionmentioning
confidence: 88%
“…In a large study (where maternal blood samples were collected early in pregnancy), Krauss et al [21] reported that mean maternal sVCAM-1 concentrations were statistically significantly elevated in women who subsequently developed preeclampsia. Results from case-control studies, where maternal sVCAM-1 concentrations were determined in blood samples collected after the clinical manifestation of preeclampsia, have consistently [17,18,20] indicated a positive association between the analyte and preeclampsia risk. Hence, on balance, available literature concerning the relation between sVCAM-1 concentrations and preeclampsia, though not as consistent as reports concerning the relation between tHcy concentrations and preeclampsia risk, suggest that elevated sVCAM-1 may be associated with preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ECAM-1 facilitates in the adhesion of trophoblast to the vascular endothelium during early pregnancy and mediates trophoblastic vascular invasion during the remodeling of placental vasculature; mediates the adhesion between the placental villi, cells in the decidual tissue, and peripheral blood leukocytes; and sustains the non-activation of decidual lymphocytes, preventing the immunological rejection of the fetus by the mother. Madazli et al (2000) reported a significant increase in the fibronectin and VCAM-1 levels in women with GH, which was correlated with the diastolic blood pressure. Krauss et al (1997) theorized that the increase in serum VCAM-1 levels reflected the activation of endothelial cells, but not cell injury, the factor responsible for predicting the development of GH and IUGR.…”
Section: Discussionmentioning
confidence: 99%
“…Os fragmentos eram assim categorizados quando não apresentavam presença de decídua e miométrio adjacente no mesmo plano de corte, ambos infiltrados, de forma inequívoca, por citotrofoblasto multinucleado. A nossa perda foi semelhante à citada na literatura por alguns autores 12,17,20 , embora um estudo 10 tenha tido uma perda de apenas 23%.…”
Section: Incisura Bilateralunclassified